ROLE OF BEVACIZUMAB FOR PREVENTION OF NEOVASCULAR GLAUCOMA IN ACUTE RETINAL VEIN OCCLUSION - Bassam Mubarik; Adeen Akram (Journal of University Medical & Dental College, 2018)
ABSTRACT:There is a possibility of developing neovascular glaucoma in ischemic type of retinal vein occlusion. Purpose of the study is to determine the role of anti VEGF agent bevacizumab for prevention of neovascular glaucoma in ischemic type of retinal vein occlusion.METHOD: It was a retrospective study of 34 cases with unilateral central retinal vein occlusion. All of them were treated with intra vitreous Bevacizumab for management of associated macular edema. Primary outcome was to study development of neovascular glaucoma in these cases.RESULTS: Thirty four cases were selected with retinal vein occlusion. Seventeen cases were of non ischemic type and remaining 17 were of ischemic type vein occlusion. During a follow up period of two years non ischemic group was given on average 8 bevacizumab injection. Only one of these non ischemic eyes developed neo vessels of optic disc but neo vascular glaucoma did not develop. In case of ischemic group during follow up period of two years a mean of 6 bevacizumab injections were given. In this ischemic group 2 cases developed iris neovesseles and 3 cases developed retinal neovesseles. Out of these, three eyes progressed to neovascular glaucoma.CONCLUSION: Bevacizumab treatment of macular edema for ischemic central retinal vein occlusion does not prevent neovascular glaucoma.